Structural Basis of Regulation of von Willebrand Factor Binding to Glycoprotein Ib - Blenner, Mark A. (American Society for Biochemistry and Molecular Biology, 2014)
Activation by elongational flow of von Willebrand factor (VWF) is critical for primary hemostasis. Mutations causing type 2B von Willebrand disease (VWD), platelet-type VWD (PT-VWD), and tensile force each increase affinity of the VWF A1 domain and platelet glycoprotein Ibα (GPIbα) for one another; however, the structural basis for these observations remains elusive. Directed evolution was used to discover a further gain-of-function mutation in A1 that shifts the long range disulfide bond by one residue. We solved multiple crystal structures of this mutant A1 and A1 containing two VWD mutations complexed with GPIbα containing two PT-VWD mutations. We observed a gained interaction between A1 and the central leucine-rich repeats (LRRs) of GPIbα, previously shown to be important at high shear stress, and verified its importance mutationally. These findings suggest that structural changes, including central GPIbα LRR-A1 contact, contribute to VWF affinity regulation. Among the mutant complexes, variation in contacts and poor complementarity between the GPIbα β-finger and the region of A1 harboring VWD mutations lead us to hypothesize that the structures are on a pathway to, but have not yet reached, a force-induced super high affinity state.